Corticosteroids in dentistry - Rishu Bhanot; Jyoti Mago (Wolters Kluwer Medknow Publications, 2016)
Steroids are one of the widely used drugs in dentistry. These are immunosuppressive agents. The reason for its use is its anti-inflammatory as well as immunosuppressive properties. Corticosteroids have revolutionized the management of several disabling conditions, but its use in term of dosage is inappropriate. The current review highlights its uses, contraindications, side-effects as well as a guideline for its use in dentistry.